TEACHER-STUDENTS’ INTERACTION PATTERNS IN ENGLISH CLASS FOR THE TENTH GRADE STUDENTS OF SMA NEGERI 1 MENGKENDEK - Rachel Rachel (Teaching English as a Foreign Language Overseas Journal, 2016)
The purpose of this research is to find out kinds of teacher-students’ interaction patternsoccur in teaching and learning process of English class for the Tenth Grade Students ofSMAN 1 Mengkendek. This research used a qualitative descriptive analysis methodresearch. The researcher took sample in this research by using snowball sampling. It usedto find out kinds of teacher-students’ interaction patterns in English class for the TenthGrade Students of SMA Negeri 1 Mengkendek. The result of data analysis indicated ofthe Tenth Grade Students of SMA Negeri 1 Mengkendek in teacher-students’ interactionpatterns in English class. The kinds of teacher-students interaction patterns used ofpattern teacher-student (A), pattern teacher-student-teacher (B), pattern of teacherstudent-students-teacher (C), and pattern teacher-student-student-teacher, and teacherstudent-student-teacher, and student-student (D).